2023
DOI: 10.3390/antibiotics12111609
|View full text |Cite
|
Sign up to set email alerts
|

Point Prevalence Survey of Antimicrobial Use and Resistance during the COVID-19 Era among Hospitals in Saudi Arabia and the Implications

Abdul Haseeb,
Safa S. Almarzoky Abuhussain,
Saleh Alghamdi
et al.

Abstract: The inappropriate prescribing of antimicrobials increases antimicrobial resistance (AMR), which poses an appreciable threat to public health, increasing morbidity and mortality. Inappropriate antimicrobial prescribing includes their prescribing in patients hospitalized with COVID-19, despite limited evidence of bacterial infections or coinfections. Knowledge of current antimicrobial utilization in Saudi Arabia is currently limited. Consequently, the objective of this study was to document current antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Given the role of antibiotic prescribing patterns in hospital settings for developing quality improvement programmes including antimicrobial stewardship programmes. Most of the point prevalence studies reported from Saudi Arabia are predominantly conducted in adults (Al-Tawfiq & Al-Homoud, 2020 ; Al Matar et al, 2019 ; AlMahasnah et al, 2023 ; Haseeb et al, 2023 ; Haseeb et al, 2022 ). Therefore, this study aimed to conduct a PPS among neonates and children admitted to different hospitals in Saudi Arabia to determine the prevalence of antibiotic use, document antibiotic prescribing practices, and provide a standardised tool for hospitals to identify gaps and the need for quality improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Given the role of antibiotic prescribing patterns in hospital settings for developing quality improvement programmes including antimicrobial stewardship programmes. Most of the point prevalence studies reported from Saudi Arabia are predominantly conducted in adults (Al-Tawfiq & Al-Homoud, 2020 ; Al Matar et al, 2019 ; AlMahasnah et al, 2023 ; Haseeb et al, 2023 ; Haseeb et al, 2022 ). Therefore, this study aimed to conduct a PPS among neonates and children admitted to different hospitals in Saudi Arabia to determine the prevalence of antibiotic use, document antibiotic prescribing practices, and provide a standardised tool for hospitals to identify gaps and the need for quality improvement.…”
Section: Introductionmentioning
confidence: 99%